Sin A - 2 Sin cube A upon 2 cos cube A - Cos A is equal to tanA
Attachments:
![](https://hi-static.z-dn.net/files/dcf/a37c551c8b55dfcfb3a332b6ac82d457.jpg)
Answers
Answered by
6
I think it helps you
Attachments:
![](https://hi-static.z-dn.net/files/d34/f9f3b01fb4516454f0e59ea0ba6b4a4a.jpg)
niahl:
mention not
Answered by
3
Hola there,
Given=>
![\frac{sin \: a - 2 {sin}^{3}a }{cos \: a - 2{cos}^{3}a } = tan \: a \frac{sin \: a - 2 {sin}^{3}a }{cos \: a - 2{cos}^{3}a } = tan \: a](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin+%5C%3A+a+-+2+%7Bsin%7D%5E%7B3%7Da+%7D%7Bcos+%5C%3A+a+-+2%7Bcos%7D%5E%7B3%7Da+%7D+%3D+tan+%5C%3A+a)
LHS
=>![\frac{sin \: a \: - 2{sin}^{3}a }{cos \: a \: - 2 {cos}^{3} a} \frac{sin \: a \: - 2{sin}^{3}a }{cos \: a \: - 2 {cos}^{3} a}](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin+%5C%3A+a+%5C%3A+-+2%7Bsin%7D%5E%7B3%7Da+%7D%7Bcos+%5C%3A+a+%5C%3A+-+2+%7Bcos%7D%5E%7B3%7D+a%7D+)
=>![\frac{sin(1 - 2{sin}^{2} a)}{cos(1 - 2{cos}^{2} a)} \frac{sin(1 - 2{sin}^{2} a)}{cos(1 - 2{cos}^{2} a)}](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin%281+-+2%7Bsin%7D%5E%7B2%7D+a%29%7D%7Bcos%281+-+2%7Bcos%7D%5E%7B2%7D+a%29%7D+)
=>![\frac{sin(1 - 2(1 - {cos}^{2} a)}{cos(1 - {cos}^{2} a)} \frac{sin(1 - 2(1 - {cos}^{2} a)}{cos(1 - {cos}^{2} a)}](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin%281+-+2%281+-+%7Bcos%7D%5E%7B2%7D+a%29%7D%7Bcos%281+-+%7Bcos%7D%5E%7B2%7D+a%29%7D+)
=>![\frac{sin(1 - {cos}^{2} a)}{cos( 1 - {cos}^{2}a) } \frac{sin(1 - {cos}^{2} a)}{cos( 1 - {cos}^{2}a) }](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin%281+-+%7Bcos%7D%5E%7B2%7D+a%29%7D%7Bcos%28+1+-+%7Bcos%7D%5E%7B2%7Da%29+%7D+)
=>![\frac{sin \: a}{cos \: a} \frac{sin \: a}{cos \: a}](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin+%5C%3A+a%7D%7Bcos+%5C%3A+a%7D+)
=>![tan \: a tan \: a](https://tex.z-dn.net/?f=tan+%5C%3A+a)
=> RHS
So, LHS = RHS
HENCE PROVED.
Hope this helps.....:)
Given=>
LHS
=>
=>
=>
=>
=>
=>
=> RHS
So, LHS = RHS
HENCE PROVED.
Hope this helps.....:)
Similar questions